2005
DOI: 10.1016/j.jtcvs.2004.07.061
|View full text |Cite
|
Sign up to set email alerts
|

Activation of neutrophils and monocytes by a leukocyte-depleting filter used throughout cardiopulmonary bypass

Abstract: The LG6 arterial line leukocyte filter is ineffective in its principal task of diminishing phagocyte activation during cardiopulmonary bypass.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
40
0
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 29 publications
1
40
0
2
Order By: Relevance
“…Rationale, obtained from the results of previous studies was supporting this idea. Very recently these opinions have been rejected by Ilmakunnas et al (8) who have found that passing of leukocytes through arterial filters was enhancing activation of neutrophils expressed as changes in CD11b/ CD18 β 2 integrins expression.…”
Section: Discussionmentioning
confidence: 99%
“…Rationale, obtained from the results of previous studies was supporting this idea. Very recently these opinions have been rejected by Ilmakunnas et al (8) who have found that passing of leukocytes through arterial filters was enhancing activation of neutrophils expressed as changes in CD11b/ CD18 β 2 integrins expression.…”
Section: Discussionmentioning
confidence: 99%
“…Perioperative complications, including systemic immune response syndrome (SIRS), myocardial and pulmonary reperfusion injury, and cerebral damage, remain critical issues during cardiac surgery procedures (2). Many studies have investigated the use of a leukocyte filter instead of a standard filter in the arterial line throughout CPB without finding evidence of sufficient filter efficiency during reperfusion (3,4). On the other hand, several authors have shown that reperfusion injury to cardiac and pulmonary tissue is diminished by leukocyte filtration (LF) in the arterial or venous line and that LF in the blood cardioplegia delivery system also enhances myocardial protection (6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, several authors have shown that reperfusion injury to cardiac and pulmonary tissue is diminished by leukocyte filtration (LF) in the arterial or venous line and that LF in the blood cardioplegia delivery system also enhances myocardial protection (6)(7)(8). The rationale for the use of leukocyte filtration is that the leukofilter substantially reduces contact of activated neutrophils with the capillary endothelium (2)(3)(4)(5)(6), thereby reducing the degree of inflammatory response and subsequent organ injury. LF has already been adapted by the blood banks to prevent leukocyte-mediated pathogenicity, and a series of experimental and clinical studies have revealed more or less beneficial effects and even contradictory results.…”
Section: Introductionmentioning
confidence: 99%
“…Κανένα από τα παρατηρούµενα οφέλη δε µεταφράζεται σταθερά σε σηµαντικό κλινικό όφελος [631][632][633][634][635]. Υπάρχουν αποδείξεις ότι η εξασθένηση των λευκών κατά την CPB µπορεί στην πραγµατικότητα να ενεργοποιήσει τα λευκά αιµοσφαίρια [636,637]. Εξαιτίας της έλλειψης κλινικού οφέλους και των ανησυχιών σχετικά µε την επιδείνωση της λειτουργίας των λευκών µε την εξασθένηση αυτών, αυτή η µέθοδος δε συστήνεται για διατήρηση αίµατος κατά την CPB.…”
Section: Viii) ∆ιηθηση λευκοκυτταρωνunclassified
“…Αντιθέτως, µια αναδροµική ανασκόπηση 1.941 χρόνων αιµορραγίας έδειξε ότι η παράταση του χρόνου αιµορραγίας µπορεί να µη σχετίζεται πάντα µε υπερβολική χειρουργική απώλεια αίµατος [776]. Τέσσερις προοπτικές µελέτες των χρόνων αιµορραγίας καθώς και της αιµορραγίας µε µέγεθος δείγµατος 118,636, 43,637, 167,638, και 112, 639 όλες έδειξαν ότι, οι παρατεταµένοι χρόνοι αιµορραγίας δε σχετίζονται µε κλινικά σηµαντική περιεγχειρητική αιµορραγία και δεν είναι αξιόπιστες δοκιµασίες ελέγχου ρουτίνας. Επιπλέον, µια θέση του Αµερικάνικου Κολλεγίου Παθολόγων και της Αµερικάνικης Εταιρείας Κλινικών Παθολόγων, δηλώνει ότι απουσία ιστορικού υπερβολικής αιµορραγίας ή άλλων υψηλού κινδύνου χαρακτηριστικών όπως η προεγχειρητική αντιαιµοπεταλιακή θεραπεία, ο χρόνος αιµορραγίας αποτυγχάνει σαν δοκιµασία ελέγχου ρουτίνας [777].…”
unclassified